Symptomatic accessory soleus muscle. Report of 18 cases in athletes - Rossi, F.; Dragoni, S. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The aim of this paper was to investigate the prevalence and sports distribution in athletes. Methods. Six hundred and fifty radiographs of athletes affected by tenderness and exertional pain in the region of the Achilles tendon, were observed over a period of 30 years. The clinical and diagnostic imaging materials were reviewed. Results: Eighteen cases of accessory symptomatic soleus muscle were diagnosed: in 10 cases using soft tissue radiographic technique, in 8 cases using, in sequence, exclusively ultrasound and magnetic resonance. Conclusion: The presence of an accessory soleus muscle has been considered a rare even incidental occurrence; the review of our cases, substantially different for the evident symptoms, showed a frequency in athletes of 2.77% in accordance with the results of the anatomical and clinical literature. US and MRI are the best diagnostic modalities especially in differentiating accessory soleus muscle from soft tissue tumors not rare in this anatomic region.